Verschmelzung von Präposition und Artikel. Eine kontrastive Analyse zum Deutschen und Italienischen - Augustin, Hagen (Konvergenz und Divergenz, 2018)
This book describes and compares at different systemic levels the contractions of prepositions and articles in German and Italian, two languages that are representative of divergent grammatical development. The author's intra and inter lingual analyses consider both diachronic and synchronic aspects and are empirically supported by large-scale quantitative and qualitative corpus investigations.